Foot Care Practices Among Diabetic Patients Visiting Public Hospitals in Rawalpindi - Rameen Tariq, Sarah Rahman, Sidra Hamid (J. Islamic Int. Med. Coll., 2021)
Objective: To assess the practices of diabetic patients visiting public hospitals of Rawalpindi with regards to diabetic foot complications and its prevention.  Study design: Descriptive cross-sectional survey. Place and Duration of study: The study was conducted in public hospitals of Rawalpindi within a duration of one and a half year. (November 2018-March 2020)  Materials and Methods: A descriptive cross-sectional survey was conducted on diabetic patients in the diabetic clinic situated in public hospitals of Rawalpindi. By using convenient sampling technique 200 patients were interviewed. Sample size was calculated using WHO calculator, with error of 5%, confidence level of 95%. Walk in (unscheduled) diabetes mellitus patients were approached and asked for willingness to participate in study after being given a brief introduction about the study. Foot care practices were compared with the examination findings. Results: The mean age of respondents was 50 ±12.44. Only 21.5% of patients were practicing good foot care 43%had satisfactory practices and 35.5% had poor practices. Education of the patients had significant statistical association with good foot care practices (p-value <0.0001). Gender also showed significant association with good foot care practices (p-value <0.013) while age and socioeconomic status had no significant statistical association with good foot care practices. Conclusion: Foot care practices adopted by the patients are highly inadequate and proper guidelines need to be provided to patients in addition to the insurance of proper foot care practices if diabetic foot associated complication is to be prevented.